A novel technique for managing infected mandibular reconstruction plates with 3D printed guide flange prostheses - N. Gopi Chander; D. Vishal Reddy; S. Shanmugasundaram; Aishwarya Roy (Oral Oncology Reports)
The technique explores an innovative application of 3D printing technology in the creation of a guide flange prosthesis for a patient who had undergone hemi-mandibulectomy and was experiencing complications due to an infected mandibular reconstruction plate. These complications not only affected the patient's functionality but also had a negative impact on their aesthetics. The issue was addressed with a 3D printed guide flange prosthesis that was custom-designed and fabricated using biocompatible resin, following the surgical removal of the infected reconstruction plate. The printed prosthesis resulted in substantial improvements in both functional and aesthetic aspects of the patient's condition. Subsequent postoperative follow-up examinations revealed no signs of infection or complications. This technique demonstrates the successful expansion of 3D printing technology into the realm of guide flange prostheses and underscores the potential for further research to evaluate the long-term efficacy of this innovative approach.